ADVANCEMENTS IN SURGERY AND MULTIMODAL GENERAL ANESTHESIA: ENHANCING PATIENT COMFORT AND MINIMIZING ADVERSE EFFECTS - Mohammed Murdhi Alshammari, Almohnd Mohamd Alqarni, Maram Fahad A Alsuwaidan, Khalaf Khalid Hadi Almutairi, Abdullah Taha Alkhaibari, Abdulaziz Saad Alatrouzi, Yousef Jamaan,; Alharbi Sultan Ali Mohammed Alhayani, Mahmood Mansour Saeed Alzaid, Omar Khalaf Alanazi, Nawaf Muqbil Saddah Aldahmashi, Waleed Saud Al Aoufi (Chelonian Research Foundation, 2022)
Multimodal general anesthesia is used in various surgical procedures, including appendectomy, total hip replacement, mastectomy, and laparoscopic cholecystectomy. These procedures involve the use of general anesthesia to ensure patient comfort and immobilization during the procedure. The induction phase involves the injection of medications to create a state of unconsciousness and forgetfulness, while the maintenance phase involves inhaled anesthetics like sevoflurane or desflurane. Opioids, such as fentanyl or remifentanil, are used to regulate pain and reduce the need for inhaled anesthetics. Balanced general anesthesia is a management approach in anesthesia care that involves the concurrent administration of various medications to induce an anesthetic state. This method was developed by anesthesiologists to prevent the maintenance of general anesthesia solely through the use of ether. By decreasing the amount of each drug administered individually during balanced general anesthesia, the probability of achieving intended effects is enhanced while the likelihood of encountering adverse effects is diminished. Opioids are used almost exclusively in this practice to control nociception intraoperatively and pain postoperatively. However, opioids have adverse effects and excessive dependence on them has contributed to the opioid pandemic in the United States. To reduce the risk of opioid overuse, balanced general anesthesia strategies are increasing the number of agents used to induce anesthesia, known as "multimodal general anesthesia." This approach aims to maximize desired effects while minimizing adverse effects, but no logical plan has been presented to determine the optimal drug combinations. The anatomy and physiology of the nociceptive and arousal circuits, as well as the mechanisms by which commonly used anesthetics and anesthetic adjuncts function in these systems, are examined in this special article. A judicious approach to multimodal general anesthesia is suggested, based on the selection of compounds that exert their effects on distinct nociceptive system targets to regulate nociception during the operation and pain afterward. Keywords: General anesthesia, operation, surgical procedures, opioids, substances, nociception control, pain management.